High-temperature, high-pressure hydrothermal synthesis, crystal structure, and infrared and NMR spectroscopy of a barium lead borate with a 2D layer structure: [Ba3Pb(H2O)][B11O19(OH)3]. Issue 19 (25th April 2020) - Kuo, Yu-Chen; Liu, Hsin-Kuan; Wang, Sue-Lein; Lii, Kwang-Hwa
Abstract : The structure of the hydrothermally synthesized barium lead borate contains an unusual fundamental building block, 2Δ4□:〈Δ2□〉–〈3□〉Δ, which was also found in the high-pressure form of CaB2 O4 synthesized at 900 °C under a pressure of 15–25 kbar. Abstract : With a high-temperature, high-pressure hydrothermal technique, a new barium lead borate, [Ba3 Pb(H2 O)][B11 O19 (OH)3 ] (1 ), has been synthesized and characterized by single-crystal X-ray diffraction, and infrared and solid-state NMR spectroscopy. The structure of 1 contains planar thick layers of borates with the Ba 2+ cations at sites in the inter- and intralayer space. Each layer consists of three single sheets. The central sheet is very corrugated and is built up from the fundamental building block (FBB) 2Δ3□:〈Δ2□〉–〈Δ2□〉. On both sides of the central sheet there are borate single chains formed of the very rare FBB 2Δ4□:〈Δ2□〉–〈3□〉Δ via corner-sharing. This FBB was first observed in a high-pressure polymorph of CaB2 O4 . These chains are linked into a sheet by PbO5 (H2 O) polyhedra, which are further linked to the central sheet by sharing vertices between triangles and tetrahedra to form a thick layer. The IR spectrum shows the presence of hydroxyl groups of HBO4, water molecules, BO3 triangles, and BO4 tetrahedra. The presence of BO3 and BO4 polyhedra was also confirmed by 11 B MAS NMR spectroscopy.